It Leaves a Bad Taste in Your Mouth: How Corporate Social Irresponsibility Impacts Consumption Experiences - Green, Todd; John Peloza; Antonia Mantonakis; Jingzhi Shang (Canadian journal of administrative sciences, 2023)
Across three experiments, we examined the impact of both corporate social responsibility (CSR) and corporate social irresponsibility (CSIR) on consumer taste evaluations. The current research demonstrates that CSIR information consistently negatively impacts perceptions of taste across both hedonic and utilitarian food products. Specifically, it translates to perceptions of inferior taste in food products, an effect mediated by both guilt and quality perceptions. Notably, the majority of CSR research focuses on attitudes toward the firm versus actual product experiences. Accordingly, firms should consider how information related to CSR/CSIR can impact not only attitudes toward the firm but the consumption experiences with specific products. Résumé En se basant sur trois expériences, les auteurs de la présente étude examinent l'impact de la responsabilité sociale des entreprises (RSE) et de l'irresponsabilité sociale des entreprises (IRSE) sur les évaluations du goût des consommateurs. Les résultats montrent que les informations relatives à la RSE ont un impact négatif constant sur la perception du goût des produits alimentaires, que ces derniers soient hédoniques ou utilitaires. Plus précisément, la perception se traduit par des impressions de goût inférieur dans les produits alimentaires, un effet que modèrent les perceptions de culpabilité et de qualité. Il convient de noter que la majorité des recherches sur la RSE portent essentiellement sur les attitudes à l’égard de l'entreprise et non sur les expériences réelles liées au produit. Par conséquent, les entreprises ont intérêt à tenir compte de la manière dont les informations relatives à la RSE/IRSE sont susceptibles d'influer non seulement sur les attitudes envers l'entreprise, mais aussi sur les expériences de consommation liées à des produits particuliers.